Education and Increasing Community Knowledge about The Benefits of Vegetables and Fruits for Hypertension Response Community Groups in Sumbersalak, Jember Regency: Edukasi dan Peningkatan Pengetahuan Komunitas tentang Manfaat Sayuran dan Buah Untuk Kelompok Masyarakat Tanggap Hipertensi di Sumbersalak Kabupaten Jember - Naretta Khoirunisak; Tantut Susanto; Miftahurroziqin, Moch Azzam; Kurdi, Fahruddin; Putra, Ary Januar Pranata; Agustina, Dina Nurul (Jurnal Pengabdian Masyarakat: Svasta Harena, 2023)
Hypertension is a global problem because the prevalence of sufferers continues to increase from year to year. Based on the results of the study, it was found that the health problem data in the Sumbersalak village community was hypertension, as many as 68 people. The aim of this activity is to improve the level of public health through community health education. This service activity is an integration of the Nursing Professional Practice which is packaged in the form of a program that focuses on the Hypertension Response Community Group (KEMASTASI) through counseling, giving pocket books, demonstrations and evaluation of assistance to the community of Sumbersalak village, Kranjingan Village, Sumbersari District, Jember Regency. The results of this KEMASASI found an increase in community knowledge and skills in maintaining health in the Sumbersalak environment from moderate to good levels.